“Beli Sekarang Bayar Nanti: Mahasiswi, Spay Later, dan Pandemi Covid-19 - Nurwahyu Ilahi (Universitas Muslim Maros, 2022)
At the time of the rise of Covid-19 in Indonesia, people had limitations in their activities, including shopping. With various policies issued by the government to limit the space for people to move in order to prevent the spread of the virus, this has made people, including female students, more stimulated to shop online. One of the e-commerce that was popular even before the Covid-19 pandemic was Shopee. Moreover, Shopee provided Shopee Pay Later (Spay Later) feature. While numbers of existing literatures deal with purchasing decision using quantitative approach and consumer legal protection, this article is focused on how female students interested in using Spay Later and how this impacted on their life. This research was conducted between September 2021 and March 2022 through social media regarding the Shopee application, using a qualitative approach. There are 15 female students who participated in this research and who use Spay Later. Data was collected using in-depth interview and observation. The study indicates that online shopping through Spay Later has increasingly stimulated because Shopee has a Spay Later feature that makes shopping easier during pandemi Covid-19. One of the Spay Later users who use this application a lot is female college students. They use Spay Later because of the convenience of shopping provided by Shopee, both in terms of shopping and payment methods. Discounted prices and postage are another reason why Spay Later is a shopping choice for female students. So even though they have no intention to shop, these offers stimulated them to shop. Shopping by using Spay Later is also an option because of the availability of various goods, anything is sold at Shopee, so shopping is like a “one stop shopping” without having to go anywhere and even if they do not have enough money to shop. It carries the slogan: